Profile of the cardiac repolarization in cervical spinal cord injury subjects performing physical exercise - Roberto Magalhães; Edgar William Martins; Alex Souto Maior; Moacir Marocolo (Universidade Estadual de Maringá, 2017)
The aim of the study was to compare rest QT interval and QTcorrected intervals of electrocardiogram in trained men with and without cervical spinal cord injury (CSCI) and investigate cardiac electrocardiogram parameters in trained men with CSCI submitted to maximal effort test. Thirty men were separated into three groups: Control without CSCI (CON, 25.3 ± 4.1 yrs, strength training: 3 days week-1; aerobic training 1day week-1; n = 10), high volume exercise (30.5 ± 4.3 yrs, 3 day week-1 rugby specific exercises, 60min. day-1; n = 12) and moderate volume of exercise (33.7 ± 5.9 yrs, 2 days week-1 specific rugby exercises, 60 min. day-1; n = 8) with incomplete CSCI (C5-C7 cervical vertrebae) more than 12 months. Electrocardiogram was recorded in rest, during and after effort test. QT interval was significantly reduced (p = 0.001) in the high volume exercise group compared to control. Corrected QT interval showed no difference between moderate vs. high volume exercise group (p > 0.05). No changes were observed in QT, corrected QT, PR and QRS intervals of electrocardiogram between rest and post effort (p > 0.05). Thus, effort test does not change electrocardiogram parameters in CSCI subjects. High volume of week exercise promotes abnormalities in cardiac repolarization compared to a moderate training program.